2023
DOI: 10.1007/s00216-022-04500-x
|View full text |Cite
|
Sign up to set email alerts
|

EOF and target PFAS analysis in surface waters affected by sewage treatment effluents in Berlin, Germany

Abstract: Per- and polyfluoroalkyl substances (PFAS) are emerging organic pollutants and can occur in surface and groundwater. To identify the degree of pollution in surface water with PFAS, often targeted HPLC–ESI–MS/MS has been employed in which commonly 30–40 compounds are analyzed. However, other PFAS and organofluorines remain undetected. We sampled surface water of the river Spree and the Teltow Canal in Berlin, Germany, which are affected by the effluent discharge of wastewater treatment plants. Here, we employed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 38 publications
0
1
1
Order By: Relevance
“…However, PFAS concentrations across all of the compartments in the study conducted in Sweden were higher than those in the present study, possibly due to the proximity of their sampling location to a military airport. Concentrations of ∑ 46 PFAS and individual congeners in surface water effluent in the current study were greater than previously reported effluent receiving surface water in Berlin, Germany (∑ 10 PFAS), which may be attributed to differences in WWTP inputs or treatments. Concentrations of individual PFAS congeners in air samples, and the overall dominance of FTOHs compared to other PFAS congeners, in the present study, were largely consistent with reported concentrations of the same individual PFAS and dominance of FTOHs in urban air samples collected globally .…”
Section: Resultscontrasting
confidence: 81%
“…However, PFAS concentrations across all of the compartments in the study conducted in Sweden were higher than those in the present study, possibly due to the proximity of their sampling location to a military airport. Concentrations of ∑ 46 PFAS and individual congeners in surface water effluent in the current study were greater than previously reported effluent receiving surface water in Berlin, Germany (∑ 10 PFAS), which may be attributed to differences in WWTP inputs or treatments. Concentrations of individual PFAS congeners in air samples, and the overall dominance of FTOHs compared to other PFAS congeners, in the present study, were largely consistent with reported concentrations of the same individual PFAS and dominance of FTOHs in urban air samples collected globally .…”
Section: Resultscontrasting
confidence: 81%
“…In their study, Nxumalo et al (2023), utilized HR-CS-GFMAS to assess extractable organically bound luorine (EOF) in surface water. The method was then compared with the quanti ied levels of PFAS identi ied through targeted analysis.…”
Section: Ongoing Activities By Research Institutesmentioning
confidence: 99%